UBVRI Light Curves of 44 Type Ia Supernovae - Jha, Saurabh (2006)
We present UBVRI photometry of 44 Type Ia supernovae (SNe Ia) observed from 1997 to 2001 as part of a continuing monitoring campaign at the Fred Lawrence Whipple Observatory of the Harvard-Smithsonian Center for Astrophysics. The data set comprises 2190 observations and is the largest homogeneously observed and reduced sample of SNe Ia to date, nearly doubling the number of well-observed, nearby SNe Ia with published multicolor CCD light curves. The large sample of U-band photometry is a unique addition, with important connections to SNe Ia observed at high redshift. The decline rate of SN Ia U-band light curves correlates well with the decline rate in other bands, as does the U-B color at maximum light. However, the U-band peak magnitudes show an increased dispersion relative to other bands even after accounting for extinction and decline rate, amounting to an additional ~40% intrinsic scatter compared to the B band.